Identifikasi Ruang Terbuka Hijau Kota Di Desa Pahandut Seberang Kota Palangka Raya: Identification of Urban Green Open Spaces in Pahandut Seberang Village, Palangka Raya City - Hamidah, Noor; Syahrozi, Syahrozi; Nindito, Dwi Anung; Santoso, Mahdi; Maulana, Muhammad Iqbal (HUTAN TROPIKA, 2025)
Pahandut Seberang Subdistrict is one of the subdistricts located in Pahandut District. Pahandut Seberang Village can be visited using land transportation or by river. Pahandut Seberang Subdistrict has a densely populated residential category. Community settlements in Pahandut Seberang Subdistrict are located on the Kahayan Riverside area, with an irregular layout and circulation patterns refer to the shape of the residence. The aim of the research is to identify green open spaces in Pahandut Seberang Subdistrict. This research uses qualitative methods by collecting secondary data from literature reviews, and primary data from interviews and observations in the field. The research analysis includes identifying the potential for river tourism, identifying the potential for developing riverside tourism and green open space in the Kahayan Riverside area, analyzing the city's green open space potential, and identifying the potential for ease of access to the Kahayan Riverside area. The results of this analysis can be used as recommendations for structuring riverside areas